Nutritive Value of Bekariya (Indigofera Cordifolia) for Camel (Camelus Dromedaril.Ls) - Mathur, C S; Purohit, G R (Annals of Arid Zone, 2016)
A conventional metabolic trial with 6 Bikaneri camels (Camelsis dromedarius) was conducted for the evaluation of the nutritive value of bekariya (Indigofera cordifolia) fodder. The average daily dry matter intake of the fodder was 2.08±0.02 kg for 100 kg body weight. The digestibility coefficients of various nutrients were: D.M. 60.95 ±2.50; C.P.66.81±1.61: E.E. 70.63±0.95; C.F. 49.06±1.58; N.F.E.61.65± 1.34 and gross energy 63.14± 1.0') Mean daily N, Ca and P balances were: -O.01±0.47·g; -6.6G±O.05 g; and -0.12±2.40 g respectively. The analyses also revealed the following values of applied nutritional importance: D.C.P ., 4.17%; T.D.N., 42.3%; N.R., 1.94 and digestible energy, 20.40 kcal per 100 kg of the feed.